2006
DOI: 10.1080/01490450600875696
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Microbial Taxa in the Subsurface Water of the Kalahari Shield, South Africa

Abstract: Microbial communities within deep subsurface environments were analyzed by 16S rRNA gene cloning. Clone libraries from 27 borehole fluid, 7 mining-contaminated, and 5 rock samples were compared. Borehole fluids derived from deep fractures were populated by microbial communities with low diversity with an average of 11 and 5 bacterial and archaeal OTUs respectively. Low taxa richness was likely driven by limited biogeochemical reactions available for growth and not extreme parameters such as pH and tempera-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
101
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 41 publications
7
101
3
1
Order By: Relevance
“…South Africa gold mine euryarchaeotic group 1 was detected at 200-1000 m and at 1300-1500 m. At 1900 and 2300 m, over 99% of the sequences were classified to Methanobacteriaceae family, causing a reduction in community evenness, diversity and richness (Supplementary Table S4). The prevalence of Proteobacteria, Firmicutes and methanogenic archaea in Outokumpu was consistent with the detection of these taxa in geographically distant continental crustal areas (Gihring et al, 2006;Sahl et al, 2008).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…South Africa gold mine euryarchaeotic group 1 was detected at 200-1000 m and at 1300-1500 m. At 1900 and 2300 m, over 99% of the sequences were classified to Methanobacteriaceae family, causing a reduction in community evenness, diversity and richness (Supplementary Table S4). The prevalence of Proteobacteria, Firmicutes and methanogenic archaea in Outokumpu was consistent with the detection of these taxa in geographically distant continental crustal areas (Gihring et al, 2006;Sahl et al, 2008).…”
Section: Resultssupporting
confidence: 81%
“…Previous studies using 16S rRNA gene cloning have reported up to 42 bacterial OTUs in continental crystalline rocks (Gihring et al, 2006;Sahl et al, 2008;Onstott et al, 2009), whereas analysis of rarefied pyrotag data obtained from Outokumpu in this study inferred 48-110 bacterial OTUs per sample (Supplementary Table S4). Archaeal OTU richness also greatly exceeded expectations based on earlier studies, with up to 112 OTUs detected in samples recovered above 1500 m (Takai et al, 2001;Sahl et al, 2008).…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…The geochemistry of the Driefontein Au Mine borehole water was consistent with groundwater from the karstic, sulfidic, Transvaal dolomite aquifer 13 . The Tau Tona Au Mine borehole water was consistent with other highly saline fracture water from >3 km depth and distinct from the mining water and acid mine drainage water in this mining district 13,15 . The 16S rRNA gene clone libraries were comprised of sulfate reducing Firmicutes and δ Proteobacteria, heterotrophic Proteobacteria (fermenters and/or methanotrophs), Nitrospira and chemolithotrophic Proteobacteria that have been previously detected in the fracture water of these mines 15 (Supplementary Tables and Discussion).…”
supporting
confidence: 57%
“…The subsurface residence time of the bulk fracture water of MP104 was on the order of tens of Ma and the Δ 2 H H2-H2O geothermometry suggested that the fracture water originated from a depth of 4.2 kmbls (Lin et al, 2006b). Other fracture water sites, ranging in depth from 0.6 to 3.2 kmbls and distributed over 300 km across the Basin, were found to contain assemblages of bacteria primarily consisting of Proteobacteria, Firmicutes, and, occasionally, a minor portion of Euryarchaeota based on the analyses of 16S rRNA genes (Takai et al, 2001;Baker et al, 2003;Moser et al, 2003;Onstott et al, 2003;Kieft et al, 2005;Gihring et al, 2006;Lin et al, 2006a;Silver et al, 2010;Davidson et al, 2011;Magnabosco et al, 2014). The surprisingly low to no observed archaeal 16S rRNA genes, the low TOC and DOC concentrations, and the low porosity (0.5% matrix, 0.01% fracture) of the Witwatersrand Basin sites distinguishes them from the more prominent archaeal communities often reported to inhabit the shallower, higher TOC bearing, higher porosity (50-90%) sub-seafloor sediments (Biddle et al, 2006).…”
Section: Introductionmentioning
confidence: 99%